A sensitive single reverse passive haemagglutination test for detecting both HBsAg and anti-HBs. - Barbara, J A (1979)
A trial of a modified reverse passive haemagglutination test for HBsAg using a 0.1% cell suspension instead of the recommended 1% showed an approximately eight-fold increase in detection sensitivity. The test can be performed within 30 minutes and lends itself to mass screening techniques. Confirmation tests can be done using the 0.1% method. In addition, the same serological plates and cells used for HBsAg screening can then be used to screen for high-titre anti-HBs. This makes the overall screening for both HBsAg and high-titre anti-HBs donors cheap and convenient.